Canonical and Non-Canonical Roles of GRK2 in Lymphocytes - Jing Cheng; Peter C. Lucas; Linda M. McAllister-Lucas (Cells, 2021)
G protein-coupled receptor kinase 2 (GRK2) is emerging as a key integrative signaling node in a variety of biological processes ranging from cell growth and proliferation to migration and chemotaxis. As such, GRK2 is now implicated as playing a role in the molecular pathogenesis of a broad group of diseases including heart failure, cancer, depression, neurodegenerative disease, and others. In addition to its long-known canonical role in the phosphorylation and desensitization of G protein-coupled receptors (GPCRs), recent studies have shown that GRK2 also modulates a diverse array of other molecular processes via newly identified GRK2 kinase substrates and via a growing number of protein-protein interaction binding partners. GRK2 belongs to the 7-member GRK family. It is a multidomain protein containing a specific N-terminal region (referred to as αN), followed by a regulator of G protein signaling homology (RH) domain, an AGC (Protein kinase A, G, C serine/threonine kinase family) kinase domain, and a C-terminal pleckstrin homology (PH) domain. GPCRs mediate the activity of many regulators of the immune system such as chemokines and leukotrienes, and thus GRK proteins may play key roles in modulating the lymphocyte response to these factors. As one of the predominant GRK family members expressed in immune cells, GRK2′s canonical and noncanonical actions play an especially significant role in normal immune cell function as well as in the development and progression of disorders of the immune system. This review summarizes our current state of knowledge of the roles of GRK2 in lymphocytes. We highlight the diverse functions of GRK2 and discuss how ongoing investigation of GRK2 in lymphocytes may inform the development of new therapies for diseases associated with lymphocyte dysregulation.